Can following formula-feeding recommendations still result in infants who are overweight or have obesity? - Ferguson, Marie C. (Pediatr Res, 2020)
BACKGROUND: Studies show that by three months, over half of US infants receive formula and guidelines play a key role in formula feeding. The question then is, what might happen if caregivers follow guidelines and, more specifically, are there situations where following guidelines can result in infants who are overweight/have obesity? METHODS: We used our “Virtual Infant” agent-based model representing infant-caregiver pairs that allowed caregivers to feed infants each day according to guidelines put forth by Johns Hopkins Medicine(JHM), Children’s Hospital of Philadelphia(CHOP), Children’s Hospital of the King’s Daughters(CHKD), and WIC. The model simulated the resulting development of the infants from birth to six months. The two sets of guidelines vary in their recommendations, and do not provide studies that support amounts at given ages. RESULTS: Simulations identified several scenarios where caregivers followed JHM/CHOP/CHKD and WIC guidelines but infants still became overweight/with obesity by six months. For JHM/CHOP/CHKD guidelines, this occurred even when caregivers adjusted feeding based on infant’s weight. For WIC guidelines, when caregivers adjusted formula amounts, infants maintained healthy weight. CONCLUSIONS: WIC guidelines may be a good starting point for caregivers who adjust as their infant grows, but the minimum amounts for JHM/CHKD/CHOP recommendations may be too high.